2010
DOI: 10.1002/acr.20084
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of varus/valgus alignment in obese individuals with knee osteoarthritis

Abstract: Objective. Frontal plane knee malalignment may increase progression of knee osteoarthritis (OA) and hasten functional decline. An accurate nonradiographic measure of knee alignment is necessary because the gold standard measure, the long-leg radiograph, is costly and often unavailable. Moreover, nonradiographic measures of knee alignment have not been validated in an obese population, where knee OA is common. The purpose of this study was to develop and assess the concurrent validity and reliability of a nonra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
13
1
3
Order By: Relevance
“…Concurrent validity between measurement methods was modest and consistent with previous studies [5][6][7][8][9][10][11]15,26], and correlations were similar when stratifying for sex and JSN. IranpourBoroujeni et al [12] reported correlations with HKA using the traditional FTA method (r ¼ 0.68) and the new FTA method (r ¼ 0.75), which were larger than those reported in the present study.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Concurrent validity between measurement methods was modest and consistent with previous studies [5][6][7][8][9][10][11]15,26], and correlations were similar when stratifying for sex and JSN. IranpourBoroujeni et al [12] reported correlations with HKA using the traditional FTA method (r ¼ 0.68) and the new FTA method (r ¼ 0.75), which were larger than those reported in the present study.…”
Section: Discussionsupporting
confidence: 87%
“…However, prior studies have highlighted its inconsistent correlations with the gold standard and traditional FTA measures (r: 0.32-0.75) [5,6,8,9,15], likely because of the low precision and large random noise of the measurement. Evaluating the relationships between goniometry and radiographic measures of alignment categorized by different directions and magnitude of uni-compartmental JSN, however, may demonstrate whether or not clinicians can utilize non-radiographic measures of alignment to identify participants with compartment-specific knee OA and/or at risk for subsequent structural progression.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Spośród ok. 13% 60-latków, u których wykazano kliniczne i radiologiczne objawy artrozy kolan, w następnej dekadzie zaawansowana lub krańcowa artroza rozwinie się u ponad 20% [2]. W przypadku osób otyłych ryzyko rozwoju zmian zwyrodnieniowych zwiększa się 3-krotnie [3]. Biorąc pod uwagę zasięg i powszechność osteo artrozy, niezwykle niepokojące są statystyki odnoszące się do jej następstw.…”
Section: Wstępunclassified
“…Among those surviving into the next decade, 20% will have symptomatic advanced or end‐stage knee OA. Obese subjects will have a three‐fold higher incidence of knee OA than the non‐obese [26] . Use of magnetic resonance imaging (MRI) may increase the sensitivity of detection and assessment of progression of knee OA [27] …”
Section: Aetiology and Pathogenesis Of Osteoarthritismentioning
confidence: 99%